Investing in a just protein transition - Wollenberg, Eva Karoline (2022)
"Investing in a just protein transition" presentation by Lini Wollenberg at the FAIRR and Clim-EAT Brainstorming session from May 17-18, 2022. Organized by the Farm Animal Investment Risk & Return (FAIRR) Initiative and Clim-Eat. The purpose of this session is to stimulate a just transition to sustainable meat production and democratize alternative meat production.